2021
DOI: 10.1142/s0217979221503124
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural, optical and electrical properties of Barium (Ba2+)- and Strontium (Sr2+)-doped Bi0.9La0.1FeO3 ceramics

Abstract: In this work, we discuss the synthesis, characterization and dielectric properties of Bi[Formula: see text]La[Formula: see text](Ba/Sr)[Formula: see text]FeO3 [[Formula: see text]] ceramic compounds. These samples were synthesized via a solid-state reaction method and then characterized for structural analysis exploiting the X-ray diffraction (XRD) technique. The Rietveld refinement data inferred that all the prepared samples were acquired a monoclinic phase with space group C1c1. Field emission scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, it has been demonstrated that the doping of Sr to La in LaCrO3 structures results in an increase in conductivity due to the production of an increased number of Cr 6+ ions [17,18]. The variation in conductivity that occurs as a function of frequency can be interpreted in a number of different ways, one of which is as the presence of space charges and cationic disorder among neighboring sites [19].…”
Section: Ac Electrical Conductivity(σac)mentioning
confidence: 99%
“…In addition, it has been demonstrated that the doping of Sr to La in LaCrO3 structures results in an increase in conductivity due to the production of an increased number of Cr 6+ ions [17,18]. The variation in conductivity that occurs as a function of frequency can be interpreted in a number of different ways, one of which is as the presence of space charges and cationic disorder among neighboring sites [19].…”
Section: Ac Electrical Conductivity(σac)mentioning
confidence: 99%